2010
DOI: 10.3389/fpsyg.2010.00171
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Theta-Burst Stimulation of the Human Cerebellum Distinguishes Absolute, Duration-Based from Relative, Beat-Based Perception of Subsecond Time Intervals

Abstract: Cerebellar functions in two types of perceptual timing were assessed: the absolute (duration-based) timing of single intervals and the relative (beat-based) timing of rhythmic sequences. Continuous transcranial magnetic theta-burst stimulation (cTBS) was applied over the medial cerebellum and performance was measured adaptively before and after stimulation. A large and significant effect was found in the TBS (n = 12) compared to the SHAM (n = 12) group for single-interval timing but not for the detection of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 69 publications
(124 reference statements)
10
92
0
1
Order By: Relevance
“…The cerebellum also responds more during learning of non-metric than metric rhythms [40]. The fMRI findings are supported by findings from other methods: deficits in encoding of single durations, but not of metric sequences, occur when cerebellar function is disrupted, either by disease [41] or through transcranial magnetic stimulation [42]. Thus, although the cerebellum is commonly activated during rhythm tasks, the evidence indicates it is involved in absolute, not relative, timing and therefore does not play a significant role in beat perception or entrainment.…”
Section: Functional Imaging Of Beat Perception and Entrainment In Humanssupporting
confidence: 71%
“…The cerebellum also responds more during learning of non-metric than metric rhythms [40]. The fMRI findings are supported by findings from other methods: deficits in encoding of single durations, but not of metric sequences, occur when cerebellar function is disrupted, either by disease [41] or through transcranial magnetic stimulation [42]. Thus, although the cerebellum is commonly activated during rhythm tasks, the evidence indicates it is involved in absolute, not relative, timing and therefore does not play a significant role in beat perception or entrainment.…”
Section: Functional Imaging Of Beat Perception and Entrainment In Humanssupporting
confidence: 71%
“…Because synchronization employs beat-based predictive timing mechanisms, it may be concluded that left dPMC is involved in beat-based timing. Continuous theta burst stimulation (cTBS), a TMS protocol that down-regulates cortical activity at the focal target location (Huang et al, 2005), interferes with interval-based timing when applied over medial cerebellum, but does not interfere with beat-based timing (Grube et al, 2010). This supports a functional dissociation between interval and beatbased timing, and suggests that cerebellum is involved in interval, but not beat-based, timing.…”
Section: Causal Studies Of Neural Circuits During Beat Perceptionmentioning
confidence: 98%
“…The auditory stream may be as simple as a metronome or as complex as a highly layered and time-varying musical work, but the human brain seems to almost automatically seek a simple regularity, the beat, or pulse, which can serve to organize our movements (as in dance, or tapping your foot to music), but also can organize our perception of time (Hannon, Snyder, Eerola, & Krumhansl, 2004;Palmer & Krumhansl, 1990). Two types of timing that are involved in rhythm perception are intervalbased (absolute) timing and beat-based (relative) timing (Dalla Bella et al, 2016;Grube, Lee, Griffiths, Barker, & Woodruff, 2010;Iversen & Balasubramaniam, 2016). Interval-based timing is common to humans and non-human primates (Merchant & Honing, 2014;Zarco, Merchant, Prado, & Mendez, 2009).…”
Section: Beat Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…by increasing tolerance against temporal variability in the processing of sequences with a regular beat. However, such mechanisms are most likely highly dependent on the specific temporal characteristics of the input, and compensation for cerebellar dysfunction may be more difficult for the timing of the absolute duration of single intervals [45].…”
Section: Discussionmentioning
confidence: 99%